Contribuição ao projeto de pavimentos de lajes sem vigas protendidas - Küster, Leandro Dias (2015)
Prestressed flat plate floor system has been an excellent structural solution for building work when there is a demand for fast construction with less manpower, where the building has height restrictions or when architecture design requires wide environments and major deformations on the floor can be avoided. Aspects like these, make the use of this structural system grow constantly. Although there are cases of built constructions, some structural engineers still feel uncomfortable to use the system, because beyond the scarcity of bibliography on this matter, most of the problems are solved by intuition, and not with technical-cientific knowledge. This research presents fundamental concepts for understanding the prestressed flat plate floor system, as well the designing methods. A comparison of the tensile stress in the slabs is also made, envolving the Equivalent Frame Method, the Finite Element Method and the Grillage Method. The effect of the lack of alignment also is studied. In sequence, examples of prestressed flat plate floor are shown and their structural solutions, using adherent and non-adherent cables, using partial prestress and reduced prestress. At the end of this research comments are made about the obtainned results and suggestions of structural solutions are presented for specific problems that occur frequently.